Factors influencing the quality and functioning of oncological multidisciplinary team meetings: results of a systematic review - Janneke E. W. Walraven; Olga L. van der Hel; J. J. M. van der Hoeven; Valery E. P. P. Lemmens; Rob H. A. Verhoeven; Ingrid M. E. Desar (BMC, 2022)
Abstract Background Discussing patients with cancer in a multidisciplinary team meeting (MDTM) is customary in cancer care worldwide and requires a significant investment in terms of funding and time. Efficient collaboration and communication between healthcare providers in all the specialisms involved is therefore crucial. However, evidence-based criteria that can guarantee high-quality functioning on the part of MDTMs are lacking. In this systematic review, we examine the factors influencing the MDTMs' efficiency, functioning and quality, and offer recommendations for improvement. Methods Relevant studies were identified by searching Medline, EMBASE, and PsycINFO databases (01-01-1990 to 09-11-2021), using different descriptions of 'MDTM' and 'neoplasm' as search terms. Inclusion criteria were: quality of MDTM, functioning of MDTM, framework and execution of MDTM, decision-making process, education, patient advocacy, patient involvement and evaluation tools. Full text assessment was performed by two individual authors and checked by a third author. Results Seventy-four articles met the inclusion criteria and five themes were identified: 1) MDTM characteristics and logistics, 2) team culture, 3) decision making, 4) education, and 5) evaluation and data collection. The quality of MDTMs improves when the meeting is scheduled, structured, prepared and attended by all core members, guided by a qualified chairperson and supported by an administrator. An appropriate amount of time per case needs to be established and streamlining of cases (i.e. discussing a predefined selection of cases rather than discussing every case) might be a way to achieve this. Patient centeredness contributes to correct diagnosis and decision making. While physicians are cautious about patients participating in their own MDTM, the majority of patients report feeling better informed without experiencing increased anxiety. Attendance at MDTMs results in closer working relationships between physicians and provides some medico-legal protection. To ensure well-functioning MDTMs in the future, junior physicians should play a prominent role in the decision-making process. Several evaluation tools have been developed to assess the functioning of MDTMs. Conclusions MDTMs would benefit from a more structured meeting, attendance of core members and especially the attending physician, streamlining of cases and structured evaluation. Patient centeredness, personal competences of MDTM participants and education are not given sufficient attention.